2014
DOI: 10.1111/aas.12258
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in‐hospital and out‐of‐hospital cardiac arrest outcomes in a Scandinavian community

Abstract: Survival from in-hospital and out-of-hospital cardiac arrest in this cohort is similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
2
21
0
2
Order By: Relevance
“…Only one study has previously compared IHCA with OHCA, and their findings are in concordance with this study as they found no difference in survival 15. Unfortunately, data on TTM were not available in that study.…”
Section: Discussionsupporting
confidence: 85%
“…Only one study has previously compared IHCA with OHCA, and their findings are in concordance with this study as they found no difference in survival 15. Unfortunately, data on TTM were not available in that study.…”
Section: Discussionsupporting
confidence: 85%
“…Data from this patient cohort have previously been published. 12 Patients with a CPC above 2 on hospital discharge and patients who could not be reached or had an unknown identity were excluded (Fig. 1).…”
Section: Patientsmentioning
confidence: 99%
“…12 HADS and EQ-5D-5L questionnaires were scored and reviewed by EAB and KKS. Data about medical history and treatment following the return of spontaneous circulation (ROSC) were retrieved retrospectively from the electronic patient journal by EAB.…”
Section: Data Handlingmentioning
confidence: 99%
“…According to the Danish Cardiac Arrest Register, 30-day survival rate after OHCA was 8.6% in 2007 and 10.1% in 2011, 2 while international reports indicate a higher survival rate of OCHA (17-22%). 3,4 Our survival of IHCA was not very high. This is not only a challenge for our institution, but for hospitals worldwide.…”
Section: Sirmentioning
confidence: 75%